Triggering Corporate Sustainable Performance in Construction Sector through Green Training: Moderating Effect of Barrier in Construction Management - WARIS, IMRAN; ÜLKÜ, İLAYDA (Yıldız Teknik Üniversitesi Rektörlüğü, 2023)
Construction barrier plays a significant but negative role-play between green training and corporate sustainability performance due to limited resources. The research question in this study is to explore the relationship between green training and sustainable performance in the construction industry, while also considering the moderating role of construction barriers. This study gives extensive knowledge of green training and corporate sustainability performance. Data is obtained from 225 employees using a convenience sampling technique from the construction sector. The research employed SPSS/PROCESS and follows a cross-sectional research design. Study findings show green training is an antecedent of the sustainable performance of the construction sector. The result shows that Green training significantly and positive role-play in sustainable performance. Person-organization fit theory covers the whole phenomenon. That focuses on productivity, performance, and personal well-being. Under P-O fit theory results are showing the compatibility between a person and an organization where they are doing work. This study's results highlight the green training that transforms the em- employee’s mindset towards corporate sustainable performance. In the future, need longitudinal studies that will be more acceptable. This study provides insights to the managers, policymakers, and practitioners of sustainable environment and performance. The current study will help economies in the developing world, such as Pakistan.
Keywords: Barrier in Construction Management; Construction Sector; Corporate Sustainable Performance; Green Training